MBiS: an efficient method for mining frequent weighted utility itemsets from quantitative databases - Ham, Nguyen Duy; Bảy, Võ Đình; Minh, Nguyen Thi Hong; Hong, Tzung-Pei (Journal of Computer Science and Cybernetics, 2015)
In recent years, methods for mining quantitative databases have been proposed. However, the processing time is fairly much, which affects the productivity of intelligent systems in the use of quantitative databases. This study proposes the multi-bit segment (MBiS) structure to store and process tidsets to increase the effeciency of mining frequent weighted utility itemsets (FWUIs) from quantitative databases. With this structure, the calculation of the intersection of tidsets between two itemsets becomes more convenient. Based on this structure, the authors define the MBiS-Tree structure and propose an algorithm for mining FWUIs from quantitative databases. Experimental results for a number of databases show that the proposed method outperforms existing methods.